2007
DOI: 10.3346/jkms.2007.22.2.290
|View full text |Cite
|
Sign up to set email alerts
|

Autocrine Extracellular Signal-regulated Kinase Activation in Normal Human Keratinocytes is not Interrupted by Calcium Triggering and is Involved in the Control of Cell Cycle at the Early Stage of Calcium-induced Differentiation

Abstract: Normal human epidermal keratinocytes (NHEK) respond to the autocrine activated extracellular signal-regulated kinase (ERK) signaling pathway, which contributes to the survival of keratinocytes. However, during the condition of calcium-induced differentiation, how the autocrine ERK signaling is regulated and affected is poorly understood. The purpose of this study was to understand and to obtain clues to the possible function of the autocrine ERK activation during the calcium-induced differentiation of NHEK. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…The MAPK pathways have been linked to keratinocyte cell survival and re‐epithelialization of skin . Previous study has suggested that Ca 2+ ‐induced activation of MAPK is important for survival of keratinocytes in early stage despite the induction of differentiation . Our data showed that Ca 2+ induced the activation of ERK, and p38 in NHEKs, which was suppressed by coculture with MSCs.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…The MAPK pathways have been linked to keratinocyte cell survival and re‐epithelialization of skin . Previous study has suggested that Ca 2+ ‐induced activation of MAPK is important for survival of keratinocytes in early stage despite the induction of differentiation . Our data showed that Ca 2+ induced the activation of ERK, and p38 in NHEKs, which was suppressed by coculture with MSCs.…”
Section: Discussionsupporting
confidence: 52%
“…Activation of MAPK pathways is critical for keratinocyte survival even during the differentiation. It is demonstrated that autocrine‐activated ERK is not interrupted by Ca 2+ triggering in keratinocytes and sustained for at least early stage of differentiation program . Our data showed that both ERK and p38 were activated in NHEKs during the Ca 2+ treatment, but significantly decreased upon coculture with MSCs.…”
Section: Resultsmentioning
confidence: 55%
“…Human epidermal keratinocytes maintain high ERK1/2 activity levels through the autocrine production of epidermal growth factor receptor ligands (Pastore et al, 2008). The transient inactivation of ERK1/2 suggests that a medium change induces a temporary lack of epidermal growth factor receptor ligands in the medium (Park et al, 2007). 2020) recently examined skin hyperesthesia in patients with chronic pruritus, such as AD, and showed that this was not related to hyperinnervation in the epidermis, as demonstrated by a decreased number of cutaneous nerves crossing the basement membrane; however, they did not report the Sema3A levels.…”
Section: Discussionmentioning
confidence: 99%
“…Involucrin and filaggrin are considered markers of keratinocyte terminal differentiation. Synthesis of involucrin starts in stratum spinosum keratinocytes, after they have stopped their division, and is considered an early marker of terminal differentiation [ 14 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. Involucrin expression could distinguish benign lesions from SCC [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%